The Concept of “Prophetic” Socialism by Max Scheler - A. N. Malinkin (Дискурс, 2021)
The article analyzes the conceptual foundations of “prophetic” socialism by Max Scheler (1874–1928). The main principles of a new political and ideological doctrine at that time, designed to become, according to the plan of its creator, an “antidote” to Marxism, are considered. The author analyzes Scheler's argumentation, directed, on the one hand, against socialism in the Marxist interpretation, and on the other, at proving the legitimacy of using the terms “Christian socialism” and “Christian prophetic socialism”. Scheler opposes socialism, first of all, to individualism, which he interprets in social and moral-philosophical senses, and only secondarily to liberalism and capitalism. Socialism and individualism, which now appear as antagonistic tendencies of sociocultural development, are for him two equally necessary and interrelated essential principles of the social being of a person, understood as a spiritual-bodily social being. Individualistic tendencies, according to Scheler, prevailed over socialist tendencies in the West in modern times, therefore socialism in its Marxist interpretation turned out to be so in demand in the late 19th and early 20th centuries. But the destruction of private property is contrary to Christianity. “Forced communism” does not bring with it heaven on earth, but catastrophe and cultural degradation, he foreshadows. Based on the teachings of the Church Fathers and starting from the Catholic social doctrine, Scheler offers his vision of an ideal society in the form of a “personal community” (Personengemeinschaft), corresponding to the true destiny of a person. In it, the individual and social principles are in harmony and interdependent development. Scheler opposes the “prophetic” method of comprehending socio-historical reality, applied proceeding from the Christian solidarism ideal, to the materialistic understanding of history. He points to three advantages of his methodology: it takes into account human freedom, the uniqueness of a historical event, combines all types and methods of human cognition, without absolutizing the scientific form of knowledge. The author reveals the deep content of Scheler's definition of Marxism as “the protest ideology of oppressed classes”, drawing on the analysis of the “sociological doctrine of idols” of the late Scheler. In it, he reveals the pre-reflexive prerequisites for the formation of class ideologies. The author points to the essential kinship of the class prejudices about which the German philosopher wrote, and the national-mental prejudices of the political elites of the leading Western countries. In conclusion, he raises the question of how relevant the problems raised in Scheler's article are today in the context of modern Russian realities.